Shallow water sound propagation over a layered calcarenite seafloor: an exercise in benchmarking various models - Koessler, Matthew; Duncan, Alexander; Gavrilov, Alexander (Australian Acoustical Society, 2013)
The sediment deficient western and southern Australian coastal seafloors consist of semi-compact layered calcarenite. Although there is a large body of work investigating and modelling the characteristics of underwater sound propagation over a layered elastic seafloor, there are still difficulties associated with modelling complex shallow water environments like the Australian shelf. For a range independent marine environment with a calcarenite bottom, the acoustic propagation characteristics have been previously modelled using numerical methods based on wavenumber integration theory. This work investigates the ability of other sound propagation models to accurately predict the acoustic field over calcarenite seafloors, specifically models based on normal mode theory. The benefits and draw-backs of this alternative modelling approach are discussed.